Diagnosis of exercise-induced bronchoconstriction: eucapnic voluntary hyperpnoea challenges identify previously undiagnosed elite athletes with exercise-induced bronchoconstriction. Issue 14 (20th July 2010) - Dickinson, John; McConnell, Alison; Whyte, Greg
Abstract : Background: There is increasing evidence to suggest many elite athletes fail to recognise and report symptoms of exercise-induced bronchoconstriction (EIB), supporting the contention that athletes should be screened routinely for EIB. Purpose: To screen elite British athletes for EIB using eucapnic voluntary hyperpnoea (EVH). Methods: 228 elite athletes provided written informed consent and completed an EVH challenge with maximal flow volume loops measured at baseline and 3, 5, 10 and 15 min following EVH. A fall of 10% in forced expiratory volume in 1 s (FEV1 ) from baseline was deemed positive. Two-way analysis of variance was conducted to compare FEV1 at baseline and maximal change following EVH between EVH-positive and EVH-negative athletes who did and did not report a previous diagnosis of EIB. Significance was assumed if p≤0.05. Results: Following the EVH challenge 78 athletes (34%) demonstrated EVH positive. 57 out of the 78 (73%) athletes who demonstrated EVH positive did not have a previous diagnosis of EIB. 30 athletes reported a previous diagnosis of asthma, nine (30%) of whom demonstrated EVH negative. There was no significant difference between the magnitude of the fall in FEV1 between athletes who reported a previous diagnosis of EIB and demonstrated EVH positive, and those with no previous diagnosis of EIB who demonstrated EVH positive (mean±SD; −21.6±16.1% vs −17.1±9.7%; p=0.07). Conclusion: The high proportion of previously undiagnosed athletes who demonstrated EVH positive suggests that elite athletes should be screened routinely for EIB using a suitable bronchoprovocation challenge.